2018
DOI: 10.5222/head.2018.001
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and Fall Behavioral in Elderly: A Study of Nursing Home

Abstract: ÖZAmaç: Huzurevinde kalan yaşlılarda mobilite ve düşme davranışlarının belirlenmesidir.Yöntem: Kesitsel tipteki bu çalışmaya 124 yaşlı birey alınmıştır. Araş-tırma verileri, tanıtıcı bilgi formu, Rivermead Mobilite İndeksi ve Yaşı-lar İçin Düşme Davranışları Ölçeği kullanılarak toplanmıştır. Bulgular: Yaş ortalaması 77±8.2 olan yaşlı bireylerin %49.2'si son bir yıl içinde en az bir kez düşmüştür ve %65.3'ü düşme korkusu yaşa-maktadır. Düşme korkusu olan, kadın olan, 81 yaş ve üzerinde olan, bedensel ve ruhsal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…In the current study, we demonstrated that more than half (69.3%) of the older people had fallen within the past 6 months, and more than half (58.9%) of them had fallen twice or more. Okuyan and Bilgili (2018) stated that 49.2% of the elderly had fallen within the last year, and 75.4% had fallen at least once. Approximately one-third of people over 65 fall every year, and more than half are repeated falls (Pohl et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we demonstrated that more than half (69.3%) of the older people had fallen within the past 6 months, and more than half (58.9%) of them had fallen twice or more. Okuyan and Bilgili (2018) stated that 49.2% of the elderly had fallen within the last year, and 75.4% had fallen at least once. Approximately one-third of people over 65 fall every year, and more than half are repeated falls (Pohl et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Okuyan ve ark. 'nın çalışmasında, huzurevinde yaşayan yaşlıların %65,3'ü düşme korkusu yaşadığı, %49,2'si son bir yıl içinde düştüğünü, son bir yıl içinde düşenlerin %75,4'ü en az bir kez düştüğünü belirtilmiştir (Birimoğlu Okuyan & Bilgili, 2018). Dünya Sağlık Örgütü 2017 yılında düşmeyi; "plansız ve ani gerçekleşen, yere, zemine veya diğer alt seviyelere gelerek, fiziksel yaralanmaya neden olan durum" olarak tanımlamaktadır (Asiri, Alshahrani, Aseeri, Alam, Ataalla, Almohiza & Abdulhamed, 2018;Rhyn & Barwick, 2019;Aktürk & İster, 2019).…”
Section: Yaşlilarda Düşmeleri̇n Epi̇demi̇yoloji̇si̇unclassified